Added Qualifications in Microsurgery: Consideration for Subspecialty Certification in Microvascular Surgery in Europe - Heidekrueger, Paul I.; Tanna, Neil; Weichman, Katie E.; Szpalski, Caroline; Tos, Pierluigi; Ninkovic, Milomir; Broer, P. Niclas (Journal of Reconstructive Microsurgery, 2016)
Background While implementation of subspecializations may increase expertise in a certain area of treatment, there also exist downsides. Aim of this study was, across several disciplines, to find out if the technique of microsurgery warrants the introduction of a “Certificate of Added Qualifications (CAQ) in microsurgery.”Methods An anonymous, web-based survey was administered to directors of microsurgical departments in Europe (n = 205). Respondents were asked, among other questions, whether they had completed a 12-month microvascular surgery fellowship and whether they believed a CAQ in microvascular surgery should be instituted.Results The response rate was 57%, and 33% of the respondents had completed a 12-month microvascular surgery fellowship.A total of 61% of all surgeons supported a CAQ in microsurgery. Answers ranged from 47% of support to 100% of support, depending on the countries surveyed.Discussion This is one of the few reports to evaluate the potential role of subspecialty certification of microvascular surgery across several European countries. The data demonstrate that the majority of directors of microsurgical departments support such a certificate. There was significantly greater support for a CAQ in microsurgery among those who have completed a formal microvascular surgery fellowship themselves.Conclusion This study supports the notion that further discussion and consideration of subspecialty certification in microvascular surgery appears necessary. There are multiple concerns surrounding this issue. Similar to the evolution of hand surgery certification, an exploratory committee of executive members of the respective medical boards and official societies may be warranted.
Keywords: reconstructive surgery; microsurgery; microvascular surgery; Certificate of Added Qualifications; curriculum